ETHOS, LOGOS, AND PERSPECTIVE - Leonte, Florin, author. ([S.l.])
1 online resource
Keywords: Ethos, Logos, and Perspective represents the first comprehensive study of late Byzantine court rhetorical praise as a general phenomenon surfacing in many types of rhetorical epideictic compositions dating from the fourteenth and the fifteenth centuries: panegyrics, encomia, city descriptions, encomiastic verses, or letters. The aim of this book is to reconstruct the two perspectives, idealism and pragmatism, that shaped authorial choices in matters of rhetorical style and composition. This study uncovers a little-known period in the history of Byzantine rhetoric. Proceeding from a nuanced understanding of the ancient concepts of ethos and logos, it analyzes the rhetoric of Byzantine praise in a modern theoretical framework. Unlike other previous studies of Byzantine rhetoric, the present research traces the structures and meanings that ultimately influenced the political attitudes and values circulating in the last century of Byzantine history. Another feature of this book is that it offers translations and discussions of important passages from the late Byzantine rhetoric, a corpus of texts that only recently has started to receive attention. This book will appeal to scholars, students, and all those interested in Byzantine literary culture (particularly in reference to moral and spiritual advice) and the techniques of Byzantine rhetoric. In addition, readers will also find informative approaches on the main authors and genres of late Byzantine rhetoric.